1987
DOI: 10.1007/bf01880103
|View full text |Cite
|
Sign up to set email alerts
|

Failure of tannic acid to inhibit digestion or reduce digestibility of plant protein in gut fluids of insect herbivores

Abstract: The rate of hydrolysis of the abundant foliar protein, ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBPC), in enzymatically active gut fluid ofManduca sexta larvae is very rapid and is unaffected by the presence of tannic acid, even when tannic acid is present in the incubation mixture in amounts in excess of the amount of RuBPC. When this protein is dissolved in the denatured gut fluids ofM. sexta larvae orSchistocerca gregaria nymphs, large amounts of tannic acid must be added to bring about the precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 33 publications
(61 reference statements)
1
64
0
1
Order By: Relevance
“…The "tannin-protein binding" mode of action has been questioned since (1) the guts of many herbivorous lepidoptera, with their high pHs and detergent content, are well adapted to prevent formation of polyphenol/protein complexes (Martin and Martin, 1984;Blytt et al, 1988), and (2) this mechanism has never been demonstrated in vivo. Martin et al (1987) showed that in Manduca sexta gut fluid hydrolyzable tannin-RUBISCO ratios must be at unity or greater for appreciable protein precipitation to occur. They suggest that such high polyphenol/protein ratios would only rarely be encountered in nature, and that protein precipitation is, therefore, probably not an ecologically relevant process.…”
Section: Discussionmentioning
confidence: 99%
“…The "tannin-protein binding" mode of action has been questioned since (1) the guts of many herbivorous lepidoptera, with their high pHs and detergent content, are well adapted to prevent formation of polyphenol/protein complexes (Martin and Martin, 1984;Blytt et al, 1988), and (2) this mechanism has never been demonstrated in vivo. Martin et al (1987) showed that in Manduca sexta gut fluid hydrolyzable tannin-RUBISCO ratios must be at unity or greater for appreciable protein precipitation to occur. They suggest that such high polyphenol/protein ratios would only rarely be encountered in nature, and that protein precipitation is, therefore, probably not an ecologically relevant process.…”
Section: Discussionmentioning
confidence: 99%
“…Within 15 min of completed GSTGmIn8H consumption by the larvae (defined as time zero), 80% of the total potential inceptin-like peptides present within the diet were recovered in the OS as active elicitors. Similarly, gut fluids of hornworm (Manduca sexta) larvae are known to efficiently proteolyze 100% of precipitable Rubisco within this same period (Martin et al, 1987). The midguts of armyworm harbor potent trypsin and chymotrypsin endopeptidase activities; thus, Lys and Phe cleavage sites near the termini of the Gm-In ( 1 KGEICDVNGVCVDAAEDEF 2 ) are predicted to facilitate this process (Keil, 1992;Paulillo et al, 2000).…”
Section: Ge1mentioning
confidence: 99%
“…For example, the principal role of tannins traditionally has been thought to be the precipitation of proteins via hydrogen bonding. Although this might occur under certain conditions, such a mechanism is ineffective against some insect herbivores, many of which have alkaline midgut and/or surfactants in their gut fluid; these prevent the formation of insoluble protein-tannin complexes (Martin et al 1987, Appel 1993. However, at high pH (e.g.…”
Section: Introductionmentioning
confidence: 99%